Influência de níveis de sombreamento no desenvolvimento de plantio juvenil de Pau-rosa (Aniba rosaeodora Ducke), na região Oeste do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2012)
We researched the effect of different levels of shade and seasonality on the photosynthetic characteristics and growth in juvenile Aniba rosaeodora trees that were cultivated in a plantation in Santarém, Pará, Brazil. The trees were between two and three years old and were submitted to four treatments: (T1) = 70% shade; (T2) = 50% shade; (T3) = 30% shade; (T4) = full sun. Variables analyzed were height and diameter growth, chloroplast pigment concentrations, chlorophyll a florescence, concentrations of essential oil, and dry mass of stem, branches, leaves and roots. The 50% and 70% shade treatments showed the highest height and diameter growth, demonstrating physiologic elasticity, and lowest growth was found for the full sun treatment. The values for chloroplast pigment concentrations were nearly equal between treatments, with small seasonal variation. Only the T4 treatment altered the photosystem II efficiency, thus inhibiting photosynthesis and growth, and the T4 and T3 treatments cause the development of photoprotection mechanisms. The largest amount of essential oil was collected from the T2 treatment, and the lowest from the T1 treatment. The T1 treatment yielded the largest amount of dry biomass and T4 the lowest. These results indicate that 50% and 70% shade strongly influenced the development of the juvenile trees and also the yield of essential oil, especially for the T2 treatment. The T4 treatment negatively influenced these variables due to the high incidence of solar radiation that directly inhibited photosynthesis.
Keywords: Pau-rosa; Óleo essencial; Fisiologia Vegetal; Amazônia; CNPQ::CIÊNCIAS EXATAS E DA TERRA; BIOPROSPECÇÃO EM RECURSOS NATURAIS